Colorectal cancer and genetic alterations in the Wnt pathway. - Segditsas, S; Tomlinson, I (2006)
In colorectal tumours, Wnt pathway genetics continues to be dominated by mutations in the adenomatous polyposis coli (APC) gene. Germline mutations cause familial adenomatous polyposis and at least two-thirds of sporadic colorectal tumours also acquire APC mutations, quite possibly as the initiating events in tumorigenesis. These mutations almost always cause loss of the C-terminal functions of the APC protein - probably involved in microtubule binding, cell polarity and chromosome segregation - and deletion of the SAMP repeats that are important for binding to axin and formation of the beta-catenin phosphorylation complex. The truncated APC proteins are, in general, stable and almost certainly retain some activity in beta-catenin binding. The 'two hits' at APC are coselected so as to produce an optimal activation of Wnt signalling (just-right hypothesis). In a minority of colorectal tumours, Wnt activation can occur through mutations that affect phosphorylation sites within exon 3 of beta-catenin, causing protein stabilization. In other tumours, epigenetic transcriptional silencing or mutation of the secreted frizzled-related proteins may modulate Wnt levels. Mutations in the Wnt components AXIN1, AXIN2 and TCF4 have been found in microsatellite-unstable colon cancers, but it is not clear in every case whether these changes are functional. Therapeutic modulation of the Wnt pathway remains an attractive therapeutic possibility for colorectal carcinomas.